2020
DOI: 10.1111/jocd.13460
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐/postprocedure measures for minimally invasive, nonenergy aesthetic treatments: A survey

Abstract: Background Non‐energy based devices used in aesthetic medicine include treatments such as microdermabrasion, microneedling, threads, and chemical peels. Practitioners may use these devices to address signs of facial photo‐ and chronological aging (fine lines, wrinkles, pigmentary, and skin textural changes). Currently, consensus papers or guidelines are lacking in peri‐procedural measures or their potential role in the prevention or treatment of adverse events in non‐energy based aesthetic procedures. Aims To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(67 citation statements)
references
References 18 publications
0
67
0
Order By: Relevance
“…[4][5][6][7][8][12][13][14][15][16][17][18][19][20][21][22][23] Two previously published surveys reported that no guidelines or algorithms are currently available concerning pre-and post-procedure measures and agents for nonenergy-based and injectable facial treatments and their use in preventing or treating post-procedural side effects or complications. 24,25 The current algorithm aims to provide clinicians with guidelines when treating patients with nonenergy-based and injectable treatments for facial rejuvenation to improve treatment outcomes.…”
Section: Literature Searchesmentioning
confidence: 99%
See 4 more Smart Citations
“…[4][5][6][7][8][12][13][14][15][16][17][18][19][20][21][22][23] Two previously published surveys reported that no guidelines or algorithms are currently available concerning pre-and post-procedure measures and agents for nonenergy-based and injectable facial treatments and their use in preventing or treating post-procedural side effects or complications. 24,25 The current algorithm aims to provide clinicians with guidelines when treating patients with nonenergy-based and injectable treatments for facial rejuvenation to improve treatment outcomes.…”
Section: Literature Searchesmentioning
confidence: 99%
“…The two previously published surveys showed that almost 95% of clinicians advised patients to avoid excessive sun exposure before, during, and after facial nonenergy-based and injectable treatments as sun exposure can contribute to postinflammatory pigment alterations or limit the effectiveness of the procedure. 24,25 To protect the face from sun exposure, broad-spectrum sunscreen with an SPF 30, or higher, is to be used and can be combined with protective measures such as wearing a wide-brimmed hat and sunglasses. 24,25 Before nonenergy-based and injectable treatments, the avoidance of alcohol, retinol peels, and agents such as acetylsalicylic acid and non-steroidal anti-inflammatory drugs (NSAIDs) amongst other agents is recommended (Table 1).…”
Section: Section 1: Preventionmentioning
confidence: 99%
See 3 more Smart Citations